Key determinants of athletic success: a Fuzzy AHP approach - Abd Aziz, Khairu Azlan; Wan Daud, Wan Suhana; Mohd Idris, Mohd Fazril Izhar; Izmi, Muhammad Amsyar; Saian, Rizauddin (UiTM Cawangan Perlis, 2025)
Athletic success is influenced by multiple factors, requiring a structured approach to identify and prioritize the key contributors to success. The Fuzzy Analytical Hierarchy Process (AHP) method provides a systematic decision-making framework to evaluate these factors by incorporating expert judgment and handling uncertainty in pairwise comparisons. This study employs the fuzzy AHP method to assess and rank the factors influencing an athlete’s successful in sports. Two experts, both lecturers from the Faculty of Sports Science and Recreation at UiTM Perlis, were involved in the evaluation due to their extensive experience and achievements in sports, making them suitable decision-makers for this study. Based on the findings, the factor of facilities plays a crucial role in sports performance, with a normalized weight of 0.4658, while coaching is identified as the most critical sub-factor, receiving a normalized weight of 0.2399. These results demonstrate that Fuzzy AHP effectively handles uncertainty and subjective judgments, providing valuable insights for athletes, coaches, and sports management in optimizing training and resource allocation.